Pengaruh Pemberian Subsidi BBM Solar terhadap Peningkatan Persepsi Keuntungan Pelaku Usaha Mikro Kecil di Kabupaten Aceh Barat - Muhaymin Muhaymin (Universitas Teuku Umar, 2023)
Diesel subsidies are very important for Micro, Small, and Medium Enterprises in the West Aceh Region. This area is a center of agriculture and industry which is experiencing difficulties where everything depends on income in terms of agriculture and fisheries. These two processes are currently very much underpinning production machines driven by diesel-powered e-engines. The purpose of this research is to see how far the perception of the recipient of the subsidy is in receiving the subsidy itself. The 63 samples for this study were taken from the database of Micro, Small, and Medium Enterprises (MSMEs) receiving diesel subsidies owned by the West Aceh District Industry and Trade Agency. From the results of the dissemination it is known that the subsidies given are still considered insufficient and need to be increased and the subsidy recipients state the amount of their income as the basis of the benefits they received.